THE EFFECTS OF TEACHING AND LEARNING MANAGEMENT USING THE MORAL PROJECTS AND REFLECTION PRACTICES ON NURSING STUDENTS’ ETHICAL BEHAVIORS - Wanchai, Ausanee; Kaewsasri, Anchalee; Srisaket, Jittiporn (Life Sciences and Environment Journal, 2017)
This quasi-experimental research aimed to compare nursing students' ethical behaviors before and after teaching method using the moral projects and reflection practices. The samples were 136 nursing students in the 2nd year, academic year 2016 of Boromarajonani College of Nursing, Buddhachinaraj, registered for ethics and laws for nursing profession course. The tools used in the study included the moral and reflection practices lesson plans and tools to collect data: a demographic data form and ethical behavior questionnaire developed by the researchers from literature review, consisted of 3 aspects: harmony, loyalty and responsibility. The data were analyzed by frequency, percentage, mean, standard deviation, and Dependent T-test. The results of the study showed that after they were taught by using the moral projects and reflection practices, the samples had a statistically significant higher overall moral behavior scores than those before taught (p <.001). Considering in each dimension, the results showed that each dimension had a statistically significant higher moral behavior scores than those before taught (p <.001).